Challenges and possibilities in the reduction of mortality due to oral cancer - Josefa Dolores Miranda Tarragó (Editorial Ciencias Médicas, 2014)
In Cuba, cancer has been the leading cause of death since 2012 (Fig.). It has displaced cardiovascular diseases and has challenged us to change this panorama. This task is not the responsibility of the Ministry of Public Health alone, but of everyone; of the population with its self-care, of the territorial organizations, of the mass media, of the commerce, of the agriculture. Therefore, this challenge must be addressed in an integral manner. Oral cancer is the sixth most common cause of death among all cancers in the world. In Cuba it is among the 10 most common in man, which has not escaped the growing trend of mortality from this disease and until the most correct strategy is found, prevention is the choice. We must direct our efforts to prevention in all its aspects such as: education, health promotion, the diagnosis of potentially malignant disorders and detection in its early stages. This entails applying the most appropriate treatments and rehabilitating patients. With regard to education, the most effective mechanisms should be sought to adequately motivate people to perform oral self-examination and become a habitual practice in families. Educate by example in relation to risk factors, insisting on the incorrect habit of smoking and the importance of an adequate diet. The mouth has a very privileged location. The stomatologist in your work has to make a thorough and orderly examination of the mouth and detect any alteration, treat it or refer the patient to the appropriate specialist, it is essential and for this no additional resources are needed. It is a humanitarian need to prevent a person from having oral cancer, because we avoid deformations and suffering for the person and their family. If we see it within the economic sphere, these treatments are very expensive for the country. From the social repercussions, because if the individual modifies its functional and psychic characteristics it stops contributing to society and also has implications in the family economy. The challenge is to modify attitudes despite the aging population. We trust in the possibilities of reducing oral cancer mortality with the efforts of all, applying the scientific advances that are available to the entire population and mobilizing all the factors of society.